2023
DOI: 10.3390/ijms241813852
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Dextran-Sodium-Sulfate-Induced Colitis in Mice through Oral Administration of Microbiome-Derived Inosine and Its Underlying Mechanisms

Weiling Guo,
Xin Tang,
Qiuxiang Zhang
et al.

Abstract: Background: Colonic and serum inosine are significantly reduced in patients with inflammatory bowel disease (IBD). Methods: This study aimed to explore whether microbiome-derived inosine alleviates colitis and its underlying mechanisms. Results: An inosine intervention effectively improved the clinical signs in colitis mice, suppressed inflammatory cytokines (tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and IL-1β) by regulating the nuclear factor-kappa B (NF-κB) pathway, and elevated the activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous research has demonstrated that intestinal microbial disorders in colitis-affected mice can be prevented by microbiome-derived inosine. This is achieved by both decreasing the abundance of pathogenic bacteria ( Pseudomonas , Acinetobacter , and Tyzzerella ) and increasing the abundance of beneficial bacteria ( Lachnospiraceae NK4A136 group , Romboutsia , Marvinbryantia , and Bifidobacterium ) [ 43 ]. Therefore, we speculated that BR could intervene to boost the proportional abundance of advantageous bacteria to intervene in rumen microbiota disturbance and preserve the health of SFWS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that intestinal microbial disorders in colitis-affected mice can be prevented by microbiome-derived inosine. This is achieved by both decreasing the abundance of pathogenic bacteria ( Pseudomonas , Acinetobacter , and Tyzzerella ) and increasing the abundance of beneficial bacteria ( Lachnospiraceae NK4A136 group , Romboutsia , Marvinbryantia , and Bifidobacterium ) [ 43 ]. Therefore, we speculated that BR could intervene to boost the proportional abundance of advantageous bacteria to intervene in rumen microbiota disturbance and preserve the health of SFWS.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides can produce SCFAs and are beneficial to the host; however, they can be opportunistic pathogens and are related to some pathological status (Shin et al, 2024). It could also be related to regulate the secretion of IL-6 and IL-17 in dendritic cells to associated with seizure severity (Xie et al, 2017).The functions of Marvinbryantia and Oscillibacter remain unclear, but they are often reported to be associated with health status or serve as protective factors (Fang et al, 2016;Xu et al, 2020;Crossland et al, 2023;Guo et al, 2023). This may be related to the production of SCFAs, which contribute to the maintenance of GM homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Several non-clinical studies have revealed the healing of experimental colitis through the recovery of TJ proteins in parallel with the improved balance of the microbiota via the administration of sinapic acid and inosine [ 100 , 101 ]. In Caco-2 cells, Lactobacillus rhamnosus CY12, a favorable Gram-positive bacterial strain, was shown to ameliorate the loss of tight junctions through lipopolysaccharide treatment by improving the expression of the tight junction proteins claudin, ZO-1, and occludin [ 102 ].…”
Section: Involvement Of the Microbiome In Changes In Tight Junctions ...mentioning
confidence: 99%